PENGARUH GAYA KEPEMIMPINAN TRANSFORMASIONAL,IKLIM ORGANISASI DAN WORK ENGAGEMENT TERHADAP JOB CRAFTING PADA KARYAWAN BANK JATENG KCPS KUDUS - Sri Haryanti; Siti Puryandani (Magisma: Jurnal Ilmiah Ekonomi dan Bisnis, 2020)
The research objectives are to (1) Know and analyze the influence of the Transformational Leadership Style on Work Engagement; (2) Knowing and analyzing the influence of Organizational Climate on Work Engagement; (3) Knowing and analyzing the effect of Work Engagement on Job Crafting. The study population was all employees of Central Java Bank KCPS Kudus as many as 30 people with saturated or census sampling techniques. This study uses SPSS software analysis tool version 25 windows and the type of data used is qualitative data derived from the results of a questionnaire which then answers respondents given a score (value) so that it becomes quantitative data, observations in the field using multiple linear regression analysis, where the regression analysis is Y = 10,782 - 0,294 X1 + 0,467 X2 + 0,782 X3, The results showed that the transformational leadership style affected work engagement, organizational climate affected work engagement and work engagement significantly influenced job crafting by 49.9% while the remaining 50.1% influenced by other variables not examined in this study. Based on these results, Bank Leaders should further enhance their adoption of transformational leadership style by being open (transparent), being able to receive constructive input and criticism from subordinates, appearing as a role model for employees, attention to problems faced related to change and encouraging employees to creating creative and innovative ideas as symbols of success